Colour matters in Balzac, from his beginnings to Séraphîta. Issue 1 (2nd January 2020) - farrant, tim
Abstract: This article explores Balzac's understanding and exploitation of colour from his beginnings to Séraphîta (1835), the ordinal end of La Comédie humaine . Beginning with his earliest philosophical writings, it considers the relative roles of the spiritual and the material, and of light and black–white binaries as absolutes versus a more nuanced evolution of colour. Falthurne and Wann-Chlore bookend a development in which La Dernière Fée pivotally mixes the referential and the symbolic. The 1830 Scènes de la vie privée, La Maison du chat-qui-pelote, and La Vendetta, stories told via colour and ways of painting, Neoclassicism and Dutch genre, are then considered. Sarrasine and Le Chef-d'œuvre inconnu's, contrasting texts presenting a monochrome-binary patterned, white sculptural supposed ideal, and an absolute colour-based incarnation of the real, are then examined. Le Chef-d'oeuvre inconnu's hands-on grappling with paint as matter takes representation beyond the colour–line dichotomy into the realm of modelling and form, and the philosophical question of the relationship between causes and effects. The article closes by comparing La Fille aux yeux d'or (1834–35) and Séraphîta, two coeval narratives at opposite ends of the moral and chromatic spectrum, but which both demonstrate contrasting ways of using colour in the quest for the Absolute.